2017
DOI: 10.1590/s0102-053620170407
|View full text |Cite
|
Sign up to set email alerts
|

Produção de couve chinesa em função da fertirrigação nitrogenada e potássica nas mudas

Abstract: A s inúmeras espécies de hortaliças da família Brassicaceae apresentam grande importância na alimentação humana, seja pela quantidade consumida, pelo alto valor nutricional ou por sua elevada produtividade. Dentre estas espécies, tem-se a couve chinesa (Brassica pekinensis). É propagada por sementes, com produção de mudas em bandejas específicas para este fim (Filgueira, 2008).A produção de mudas consiste em uma das etapas mais importantes do sistema produtivo hortícola, necessitando utilização de insumos de a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Silva et al (2018), studying the effect of nitrogen and potassium doses on the production of broccoli seedlings, observed higher values of plant height, stem diameter, and shoot dry matter when applied the highest dose of N (240 mg.L -1 ). Cardoso et al (2017) reported a linear increase in the vegetative traits of Chinese cabbage (Brassica pekinensis) seedlings, the higher the applied nitrogen dose. 018 CV% Coefficient of variation, *** SEM-Standard error of the mean.…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2018), studying the effect of nitrogen and potassium doses on the production of broccoli seedlings, observed higher values of plant height, stem diameter, and shoot dry matter when applied the highest dose of N (240 mg.L -1 ). Cardoso et al (2017) reported a linear increase in the vegetative traits of Chinese cabbage (Brassica pekinensis) seedlings, the higher the applied nitrogen dose. 018 CV% Coefficient of variation, *** SEM-Standard error of the mean.…”
Section: Resultsmentioning
confidence: 99%
“…A produção de mudas é uma das etapas mais importantes do sistema produtivo de hortaliças, que necessita da utilização de insumos de alta qualidade, sendo o substrato o de maior importância (Cardoso et al, 2017). Após a seleção de um substrato, vários fatores devem ser levados em consideração para a produção de uma boa muda, sendo estes: profundidade da semeadura, sementes de qualidade e manejo de irrigação (Dutra et al, 2016).…”
Section: Introductionunclassified